Penerapan Teknologi Blockchain Sebagai Media Pengamanan Proses Transaksi E-Commerce - Untung Rahardja; Qurotul Aini; Muhamad Yusup; Aulia Edliyanti (CESS (Journal of Computer Engineering, System and Science), 2020)
The application of blockchain technology in an E-commerce service is a necessity in the transaction processing required by a security system to ensure data confidentiality.Through the SWOT method, blockchain technology can be applied as a security medium in the e-commerce transaction process. Unfortunately there are still very few e-commerce industries that use a blockchain-based platform, so there is still a lack of trust in the security of safe and decentralized business transactions.Specifically, there are 2 benefits of this research, the first is the security system for transaction processing through the implementation of the blockchain and the second is the payment system that is easier, more efficient and well documented. Please for students, lecturers and other parties in the transaction process. The use of Blockchain technology to streamline identity management, build approved systems and manage product authenticity, and is expected to synchronize data stored in the blockchain to all user networks. can make payment systems easier, more efficient and well-defined. Please for students, lecturers and other parties in the transaction process.